PENGARUH E-SERVICE QUALITY DAN BRAND TRUST TERHADAP KEPUTUSAN PEMBELIAN PADA TRAVELOKA.COM (STUDI PADA KONSUMEN TRAVELOKA.COM KOTA SEMARANG) - Dendy Maulana Rosyidin; Apriatni Endang Prihatini (Jurnal Ilmu Administrasi Bisnis, 2020)
Online Travel Agent (OTA) is a travel agent with sales based on online or through a website provided by the company to be able to meet the needs of consumers. Traveloka.com is one of the Indonesian companies engaged in OTA. Traveloka.com also received the award from BrandZ and The Most Innovative Brand in 2017. This study aims to determine the effect of e-service quality and brand trust on the purchasing decision of Traveloka.com. This research’s type is explanatory research and the sampling method use nonprobability sampling and purposive sampling methods.Data collection uses google form. The samples are 100 respondents using Traveloka.com services in Semarang City. This research uses quantitative and qualitative analysis with validity, reliability, correlation coefficient, determination coefficient, simple and multiple regression, the significance of t and F test. The result shows that e-service quality and brand trust variables influence Traveloka.com’s purchasing decisions. The correlation coefficient of e-service quality and brand trust variables on purchasing decisions have a strong effect. The determination coefficient of the e-service quality variable on Traveloka.com’s purchasing decisions is 36,3 percents and the determination coefficient of the brand trust variable on Traveloka.com’s Purchasing decision is 37,5 percents.